Comparative analysis of total hip arthroplasty versus hemiarthroplasty for femoral neck fractures: a systematic review - Sharma, Neel; Rathi, Pranav; Devpura, Mukesh; Deshpande , Sandeep (International Journal of Research in Orthopaedics, 2026)
Displaced femoral neck fractures (FNFs) are among the most common and debilitating injuries in elderly. The optimal surgical management-total hip arthroplasty (THA) or hemiarthroplasty (HA), remains a subject of debate. This study aimed to compare clinical outcomes reported in literature of patients with a femoral neck fracture treated with either hemiarthroplasty or total hip arthroplasty (THA).This review incorporates findings from landmark randomized controlled trials (RCTs), meta-analyses, and major guidelines, including NICE (2023), Falotico et al (2025) , the HEALTH trial (2019) , Ekhtiari et al (2020), Tang et al (2020) , Lewis et al (2019) , and large registry analyses Edelstein et al 2023 which included population based retrospective studies of elderly >65 years of age with neck of femur fracture. Across over 60,000 patients, mortality rates were similar between THA and HA. THA demonstrated modest improvements in medium-term function and quality of life, particularly in cognitively intact, independent patients. However, THA carried a higher dislocation risk and required longer operative time and greater blood loss. Revision and reoperation rates were comparable. Cost-effectiveness analyses favoured THA in healthy, active individuals but not in frail or dependent patients. Our study concludes that THA offers small functional advantages but with higher dislocation risk. Procedure choice should be individualized based on patient health, functional status, and life expectancy. HA remains appropriate for frail or low-demand patients.